(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
A new subspecies of Neogloboquadrina atlantica atlantica previously reported under different names, is here distinguished and named Neogloboquadrina atlantica praeatlantica. Its first occurrence into the Mediterranean dated at 11.78 Ma, is not evolutionary appearance but is related to a global climatic cooling which pushed southwards from high latitude this taxon; however, the area of its evolutionary appearance is not clearly defined; its extinction occurs within the Globigerinoides obliquus extremus Zone. N. atlantica atlantica which evolves from N. atlantica praeatlantica occurs in the Mediterranean at 11.15 Ma, just after the Mediterranean exit of Paragloborotalia siakensis (Le Roy).